Maternal history of maltreatment and offspring's emotional and behavioral problems in adolescence: Do family factors contribute to the intergenerational risk transmission? - Bravo, Patricia; Kim, Yugyun; Xerxa, Yllza; Koopman-Verhoeff, M. Elisabeth; Carcamo, Rodrigo; Oldehinkel, Albertine; Hillegers, Manon; Jansen, Pauline (My University, 2023)
Background: A history of childhood maltreatment often has a negative and long-lasting impact across different domains in life. A childhood maltreatment experience in parents may even affect the next generation. So far, the effects of family factors have been considered in the intergenerational transmission of adversity across the childhood years, but whether the effects remain until adolescence is less clear. Objective: Using data from a large population-based study in the Netherlands, including both mother and child reports, we examined whether maternal childhood maltreatment history is associated with increased mental health problems in offspring and the role of family functioning and harsh parenting as a potential pathway. Participants: 4912 adolescents (aged 13 years) and their mothers were recruited in the Generation R study. Methods: Mothers reported childhood maltreatment experiences using the Childhood Trauma Questionnaire (CTQ), and adolescents reported on their mental health using the Youth Self Report (YSR). Structural equation modeling (SEM) was used to test the association of maternal childhood maltreatment on mental health problems in offspring and family functioning and harsh parenting as mechanisms to explain this association. Results: Adolescents of mothers with a history of maltreatment had greater internalizing (beta = 0.07, p < .01) and externalizing problems (beta = 0.08, p < .01). Moreover, we found an indirect effect via family functioning over time and harsh parenting at ages 3 and 8 years which mediated this association. Conclusion: We concluded an intergenerational effect of maternal childhood maltreatment on adolescents internalizing and externalizing problems. The findings might enable earlier intervention within the family context to mitigate the consequences of maternal childhood maltreatment.
Keywords: child maltreatment; longitudinal research; internalizing problems; externalizing problems; family functioning; harsh parenting